Metal ions and sugar puckering balance single-molecule kinetic heterogeneity in RNA and DNA tertiary contacts - Fabio D. Steffen (Nature Portfolio, 2020)
Mobile group II introns function as ribozymes to splice and reinsert themselves into DNA, thereby colonizing new genomic regions. Here the authors use single-molecule FRET and molecular dynamics simulations to reveal a structural link between metal ion induced kinetic heterogeneity and the sugar puckers at the exon-intron binding interface.